Direct conversion of chitosan to 5-hydroxymethylfurfural in water using Brønsted–Lewis acidic ionic liquids as catalysts. Issue 105 (31st October 2016) - Jiang, Yi; Zang, Hongjun; Han, Sheng; Yan, Bing; Yu, Songbai; Cheng, Bowen
Abstract : The dehydration of chitosan to 5-hydroxymethylfurfural (HMF) via hydrothermal conversion was investigated in the presence of Brønsted–Lewis acidic ionic liquids. Abstract : The dehydration of chitosan to 5-hydroxymethylfurfural (HMF) via hydrothermal conversion was investigated in the presence of Brønsted–Lewis acidic ionic liquids. The catalytic effect of different Brønsted- and Lewis-acidic sites and the molar fraction of Lewis-acidic sites were investigated in detail. It was found that Brønsted–Lewis acidic ionic liquids ([Hmim][HSO4 ]–0.5FeCl2 ) exhibited good catalytic performance, furnishing HMF in 44.11% yield. Furthermore, the effects of reaction temperature, time, and amount of catalyst were also investigated. The optimal reaction conditions were obtained for a 1.25 wt% aqueous solution of the catalyst under hydrothermal conditions (180 °C for 4 h). A high HMF yield of 44.11% was obtained starting from 50 mg of chitosan. The Brønsted–Lewis acidic ionic liquid catalysts could be recycled by simple separation and exhibited constant activity in four successive trials.